Variability of Dominant Endophytic Fungi Associated with Nypa fruticans and Selected Water Parameters in Kuching Wetland National Park (KWNP), Sarawak - Nuraini, Binti Mohd Sabri (Universiti Malaysia Sarawak (UNIMAS), 2014)
A research was done in Kuching Wetland National Park (KWNP), Sarawak to analyse the basic physicochemical water properties of KWNP, the dominancy of endophytic fungi that associated with Nypa fruticans as well as to relate the dominant endophytic fungi with respects to the variability of the water parameters. The present study involved the combination of water parameters assessments, fungal screening in heavy metals and molecular techniques. Sampling was carried out on September 2013 and selected water parameters; pH, temperature, salinity, turbidity, total suspended solids and nutrients were analysed. A sample of Nypa fruticans from each sampling stations were taken for endophytic fungi works. The range of environmental conditions; pH, temperature, salinity, turbidity and total suspended solids are 8.0 to 8.6,28.29 to 29.49 °C, 7 to 22 PSU, 833.7 to 1561.07 NTU and 0.017 to 0.123 mg/L, respectively. Based on the result ofwater parameters, five representative sites were chosen. Endophytic fungal isolates from these five stations were screened in two concentrations (500 ppm and 1000 ppm) of four heavy metals; Zinc (Zn), Lead (Pb), Copper (Co) and Chromium (Cr)to select the dominant fungal isolates. A total of 8 isolates were able to grow, three isolates can resist in Zn, Pb and Co while the other five isolates can resists in Zn, Pb and Cr. Molecular techniques done using Internal Transcribed Spacer (ITS), ITS 1 and ITS4 as primers. Phylogenetic tree constructed supported the morphological identification of Isolate 2, 3, 4, 6, 7 and 8, which is Pestalotiopsis sp. Pestalotiopsis sp were identified to have high tolerance on wide environmental conditions. Future research on morphology should be done using Scanning Electron Microscope or Transmission Electron Microscope to further distinguish and correctly defined the species ofendophytic fungi.